URGENSI ULUM Al-HADIS DALAM MEMAHAMI Al-QURâAN DAN STATUS HADIS - Kamaruddin, Kamaruddin (Institut Agama Islam Negeri (IAIN) Palu, 2005)
This article discusses functions of hadith to Qurâan. It elucidates role of hadis in elaborating meanings contained in Qurâan. It is found that there are some functions of hadith to Qurâan such as bayan al-tafsir (exegesing commentary), bayan al-tauqid (conforming commentary), bayan al-tahqiq (inquiring commentary) and bayan al-tasyri (law-enacting commentary). This article also suggests role of ulum al-hadith in investigating hadith validity level.Â Kata Kunci: Ulum al-Hadis, Al-Qurâan, Hadis